Topical fluoride and regulation of salivary pH in Peruvian Altiplano schoolchildren: a comparative longitudinal study - Mamani-Cori, Vilma; Calcina-Asillo, Talia Paola; Chino-Mamani, Marleny; Mendoza-Quispe, Yang Rodrigo; Yucra-Sardón, Sidgar Orlando; Arbildo-Vega, Heber Isac; Padilla-Cáceres, Tania Carola; Quispe-Quispe, Betsy; Coronel-Zubiate, Franz Tito (Frontiers in Oral Health, 2025)
IntroductionSaliva acts as a natural buffer, neutralizing the acids produced by bacterial metabolism. Maintaining salivary pH in a range close to neutrality is essential for enamel remineralization processes. This study aimed to evaluate and compare the effect of different concentrations and formulations of topical fluoride on the regulation of salivary pH in schoolchildren from the Altiplano region of Peru.MethodA quantitative, longitudinal, double-blind, randomized experimental design was employed. A total of 200 children aged 6–12 years who voluntarily agreed to participate were randomly and equally distributed into four study groups. To ensure homogeneous assignment, sociodemographic variables (sex, family type, age, number of siblings, and frequency of daily brushing) and clinical variables (caries severity and oral hygiene level) were controlled. Data were analyzed using SPSS version 25.0. The Shapiro–Wilk test assessed normality (p < 0.05), while Kruskal–Wallis test was used for between-group comparisons and the Friedman test for intragroup comparisons.ResultsIntragroup analysis revealed statistically differences in salivary pH at initial, post-brushing, 10, 30, 60 min and 24-hours measurements across all groups (Friedman's Test; p < 0.001). Between-group comparisons also showed significant differences in salivary pH at 10, 30, 60 min, and at 24 and 48 h (Kruskal–Wallis test; p < 0.05).ConclusionIn conclusion, the 5% fluoride varnish and fluoride gels (1.23% and 2%) demonstrated greater efficacy in regulating salivary pH, especially during the initial hours following application.